2013
DOI: 10.1166/jbn.2013.1602
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble and Biocompatible MnO@PVP Nanoparticles for MR Imaging <I>In Vitro</I> and <I>In Vivo</I>

Abstract: The uniform-sized manganese oxide nanoparticles (the oleic-capped MnO NPs) were synthesized by the thermal decomposition of Mn-oleate complex and were transferred into water with the help of cationic surfactant of cetyltrimethyl ammonium bromide (CTAB), then the poly(vinylpyrrolidone) (PVP) membrane was further coated on to them with the aid of anionic dispersant of poly(styrenesulfonate) (PSS) by layer-by-layer electrostatic assembly to render them water soluble and biocompatible. They were characterized by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…The peaks at 520 and 433 cm À1 refer to the metal-oxygen stretching vibrations of Ce-O and Mn-O. 40,43 The SEM images of Ce(NO 3 ) 3 -MnAc/PVP NFs and CeMnO 3 NFs are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 520 and 433 cm À1 refer to the metal-oxygen stretching vibrations of Ce-O and Mn-O. 40,43 The SEM images of Ce(NO 3 ) 3 -MnAc/PVP NFs and CeMnO 3 NFs are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…The relaxivity value specifies the ability to contrast the image by brightening specific tissues; therefore, agents with higher relaxivity can be administered at a lower dose, which increases their safety. Another nanomaterial, MnO NPs coated with polyvinylpyrrolidone (PVP), turned out to have good contrasting properties in MRI, enhancing the brightness in a dose-dependent manner [ 24 ]. Mn 3 O 4 NPs modified with polyethylene glycol (PEG) and fluorescent dye from the cyanine group (Cy 7.5 ), developed by Zhan et al [ 25 ], allowed a dual-modality imaging based on magnetic resonance and fluorescence.…”
Section: Medical Applications Of Manganese and Manganese Oxide Nanoparticlesmentioning
confidence: 99%
“…MnO NPs functionalised with PVP, designed as an MRI contrasting agent, were investigated for their uptake and cytotoxicity. After a 24-h treatment of human lung carcinoma cells (SPCA-1), no differences in viability between treated and control cells were observed [ 24 ]. Cytotoxicity study, performed by Bi et al [ 38 ] as a part of new theranostic tool development, showed no cytotoxic effect of MnO 2 nanosheets on L929 fibroblast cells.…”
Section: Analysis Of the Biological Impact Of Nano-sized Manganese Compoundsmentioning
confidence: 99%
“…In particular, MnO@PVP NPs can pass through the blood–brain barrier (BBB) and gradually metabolize to other sites with blood flow. This is indicated as an intravascular MRI CA (r 1 =1.937 mM −1 s −1 , r 2 =27.879 mM −1 s −1 , 3.0 T) and a potential application in basic neuroscience research 35. Hsu et al encapsulated MONPs with silica-F127 (PEO 106 PPO 70 PEO 106 ) in order to make them highly hydrophilic.…”
Section: Mno-based Nanoparticles In Tumor Diagnosis and Therapymentioning
confidence: 99%